Histone Acetylation Defects in Brain Precursor Cells: A Potential Pathogenic Mechanism Causing Proliferation and Differentiation Dysfunctions in Mitochondrial Aspartate-Glutamate Carrier Isoform 1 Deficiency - Poeta, Eleonora; Petralla, Sabrina; Babini, Giorgia; Renzi, Brunaldo; Celauro, Luigi; Magnifico, Maria Chiara; Barile, Simona Nicole; Masotti, Martina; De Chirico, Francesca; Massenzio, Francesca; Viggiano, Luigi; Palmieri, Luigi; et al. (Frontiers in Cellular Neuroscience, 2022)
AGC1 deficiency is an ultra-rare genetic disease characterized by global hypomyelination and brain atrophy, caused by mutations in SLC25A12 gene leading to a reduction in mitochondrial aspartate-glutamate carrier 1 (AGC1) activity. In both neuronal and oligodendrocytes precursor cells (NPCs and OPCs), it determines reduced proliferation with an accelerated OPCs differentiation, both associated with gene expression dysregulation. Epigenetic regulation of gene expression through histone acetylation plays a crucial role in both NPCs and OPCs proliferation/differentiation and is modulated by mitochondrial metabolism. In AGC1 deficiency models, both OPCs and NPCs show an altered expression of transcription factors involved in brain precursor cells proliferation/differentiation, as well as a reduction in histone acetylation with a parallel alteration in HATs and HDACs expression and activity. Here, histone acetylation dysfunctions have been dissected in in vitro models of AGC1 deficiency OPCs (Oli-Neu cells) and NPCs (neurospheres) , in physiological condition and following pharmacological treatments. HATs inhibition by curcumin arrests OPCs proliferation leading to their differentiation, while HDACs inhibition by SAHA has only a limited effect on proliferation, but it significantly stimulates OPCs differentiation. In NPCs, both treatments determine an alteration in the commitment towards glial cells. These data contribute to clarify the molecular and epigenetic mechanisms regulating OPCs and NPCs proliferation/differentiation. This will help to identify potential targets for new therapeutic approaches able to increase the OPCs pool and to sustain their differentiation towards oligodendrocytes and therefore myelination/remyelination processes in AGC1 deficiency, as well as in other white matter neuropathologies.